Simulation for Teaching Orthopaedic Residents in a Competency-based Curriculum: Do the Benefits Justify the Increased Costs? - Nousiainen, Markku T. (Clin Orthop Relat Res, 2015)
BACKGROUND: Although simulation-based training is becoming widespread in surgical education and research supports its use, one major limitation is cost. Until now, little has been published on the costs of simulation in residency training. At the University of Toronto, a novel competency-based curriculum in orthopaedic surgery has been implemented for training selected residents, which makes extensive use of simulation. Despite the benefits of this intensive approach to simulation, there is a need to consider its financial implications and demands on faculty time. QUESTIONS/PURPOSES: This study presents a cost and faculty work-hours analysis of implementing simulation as a teaching and evaluation tool in the University of Toronto’s novel competency-based curriculum program compared with the historic costs of using simulation in the residency training program. METHODS: All invoices for simulation training were reviewed to determine the financial costs before and after implementation of the competency-based curriculum. Invoice items included costs for cadavers, artificial models, skills laboratory labor, associated materials, and standardized patients. Costs related to the surgical skills laboratory rental fees and orthopaedic implants were waived as a result of special arrangements with the skills laboratory and implant vendors. Although faculty time was not reimbursed, faculty hours dedicated to simulation were also evaluated. The academic year of 2008 to 2009 was chosen to represent an academic year that preceded the introduction of the competency-based curriculum. During this year, 12 residents used simulation for teaching. The academic year of 2010 to 2011 was chosen to represent an academic year when the competency-based curriculum training program was functioning parallel but separate from the regular stream of training. In this year, six residents used simulation for teaching and assessment. The academic year of 2012 to 2013 was chosen to represent an academic year when simulation was used equally among the competency-based curriculum and regular stream residents for teaching (60 residents) and among 14 competency-based curriculum residents and 21 regular stream residents for assessment. RESULTS: The total costs of using simulation to teach and assess all residents in the competency-based curriculum and regular stream programs (academic year 2012–2013) (CDN 155,750, USD 158,050) were approximately 15 times higher than the cost of using simulation to teach residents before the implementation of the competency-based curriculum (academic year 2008–2009) (CDN 10,090, USD 11,140). The number of hours spent teaching and assessing trainees increased from 96 to 317 hours during this period, representing a threefold increase. CONCLUSIONS: Although the financial costs and time demands on faculty in running the simulation program in the new competency-based curriculum at the University of Toronto have been substantial, augmented learner and trainer satisfaction has been accompanied by direct evidence of improved and more efficient learning outcomes. CLINICAL RELEVANCE: The higher costs and demands on faculty time associated with implementing simulation for teaching and assessment must be considered when it is used to enhance surgical training.